Genesis of high hexavalent chromium groundwater in deep aquifers from loess plateau of Northern Shaanxi, China. (1st June 2022) - Yan, Song; Guo, Huaming; Yin, Jiahong; Hu, Huiying; Cui, Di; Gao, Bingying
Highlights: High Cr groundwater was mainly concentrated in deep aquifers in Loess Plateau. Chromium was mainly in silicates-bound form, followed by strongly adsorbed form. Silicate weathering was the dominant water-rock interaction in the deep aquifers. Mn oxides were the main oxidant for Cr(III) oxidation into Cr(VI) in the aquifers. Relatively high pH and ionic strength mobilized the adsorbed Cr(VI) via desorption. Abstract: Hexavalent chromium (Cr(VI)) groundwater usually exists in shallow aquifers related to ultramafic and serpentine formations, but knowledge of the genesis of dissolved Cr(VI) in deep sandstone aquifers is limited. Both groundwater and aquifer sediments were taken from the Jingbian County in the Loess Plateau of Northwestern Shaanxi to investigate distribution and genesis mechanism of high Cr(VI) groundwater in deep sandstone aquifers. Results showed that the Cr concentrations (median 142 μg/L) in groundwater from deep aquifers (>100 m) were relatively high, while the Cr concentrations in shallow groundwater were low (median 33.8 μg/L). Dissolved Cr mainly existed in the species of Cr(VI) (average, 90%). Deep groundwater with higher Cr(VI) concentrations generally had higher pH, Eh, and DO than shallow groundwater, indicating that the high Cr(VI) groundwater existed in relatively oxic environment. Cretaceous sandstones in deep aquifers had anomalously high contents of total Cr (average 115 mg/kg), where Cr was mainly present in silicates-bound form, and secondly in strongly adsorbed form. There were positive correlations between Mn and Cr in the unweathered silicate-bound form and adsorbed form, which were conducive to Cr(III) oxidation into Cr(VI) in an alkaline-oxic environment. The different ionic ratios (i.e. ( Ca 2+  + Mg 2+ )/(HCO3 −  + SO4 2− )) also supported silicate weathering as the dominant rock-water interactions in the deep groundwater, which enhanced the release of the unweathered silicate-bound Cr. Relatively high pH and ionic strength mobilized the adsorbed Cr(VI) into groundwater. This investigation emphasizes the geological origin of high Cr(VI) groundwater in deep sandstone aquifers containing Mn oxides, which deserves more concerns for the purpose of drinking water supply. Graphical Abstract: Image, graphical abstract